Staging Inclusion A Systematic Review of Sustainable Inclusive Theatre Production within the Framework of the SDGs - Setyo Yanuartuti (Proceeding of International Joint Conference on UNESA, 2025)
Inclusive theatre production remains largely incidental and limited to short-term projects, lacking a well-established model of sustainability. In many cases, inclusion is reduced to technical accessibility rather than genuine creative participation. Addressing this gap, the present study aims to map the practices, strategies, and sustainability orientations in inclusive theatre production and to examine its contribution to the Sustainable Development Goals (SDGs). The research employs a Systematic Literature Review (SLR) based on the PRISMA 2020 protocol, with data retrieved from Scopus, Web of Science, and Google Scholar (2020–2025). Out of 50 initial publications, 23 studies met the inclusion criteria and were analyzed through thematic analysis. The findings reveal four key insights. First, conceptually, inclusive theatre is no longer viewed merely as an accessibility tool but as a social practice that negotiates identity and power relations through co-creation rather than symbolic representation. Second, in terms of production methods, approaches such as disability-led theatre, applied theatre, and community-based performance emerge as dominant models that foster equitable participation. Third, integration with the SDGs is reflected in the implementation of ecotheatre, dramatherapy, and arts-based pedagogy, which align with SDG 3, 4, 10, 11, and 12. Fourth, ongoing challenges include policy reform, the equalization of artistic authority, and the strengthening of collective leadership. In conclusion, inclusive theatre holds a strategic position as a transformative instrument for sustainable development, provided it is supported by a consistent and participatory cross-sectoral ecosystem.